TRANSPARENCY OF ONLINE LOAN INFORMATION: ANALYSIS OF DISCLOSURE OF INTEREST RATES, TERMS, ADDITIONAL FEES, AND LATE PAYMENT PENALTIES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyse the level of information transparency in online loan applications in Indonesia, focusing on four main aspects, namely interest rate disclosure, loan terms, additional costs, and late payment penalties. The background to this study stems from the phenomenon of the proliferation of online loan services that offer easy access to financing, but are often accompanied by significant risks due to the lack of clear and easily understandable information for consumers. The method used is descriptive qualitative with a content analysis approach, where primary data is obtained through direct review of official and unofficial online loan applications, while secondary data is collected from academic literature, regulatory reports, and related publications. The results of the study show that most online loan applications still do not fully comply with the principle of information disclosure. Interest rates are often displayed only on a daily basis, obscuring the effective annual interest rate, the term is not always disclosed in detail from the outset, additional costs often appear in the form of hidden deductions, and late fees are rarely clearly explained with a transparent calculation mechanism. This situation not only has the potential to harm consumers financially, but also has an impact on psychological aspects and reduces the level of trust in the fintech lending industry as a whole. The implications of this study emphasise the importance of the active involvement of three main parties, namely online loan providers, regulators, and consumers. Service providers are expected to increase transparency with clear and uniform information standards; regulators such as the OJK and AFPI need to tighten supervision and set disclosure standards based on the Annual Percentage Rate (APR); while consumers need to continue to improve their financial literacy in order to be able to critically assess risks. With this synergy, it is hoped that online lending services can develop in a healthier, fairer, and more sustainable manner in supporting financial inclusion in Indonesia.